Mammalian Host-Versus-Phage immune response determines phage fate in vivo - Hodyra-Stefaniak, Katarzyna (Sci Rep, 2015)
Emerging bacterial antibiotic resistance draws attention to bacteriophages as a therapeutic alternative to treat bacterial infection. Examples of phage that combat bacteria abound. However, despite careful testing of antibacterial activity in vitro, failures nevertheless commonly occur. We investigated immunological response of phage antibacterial potency in vivo. Anti-phage activity of phagocytes, antibodies, and serum complement were identified by direct testing and by high-resolution fluorescent microscopy. We accommodated the experimental data into a mathematical model. We propose a universal schema of innate and adaptive immunity impact on phage pharmacokinetics, based on the results of our numerical simulations. We found that the mammalian-host response to infecting bacteria causes the concomitant removal of phage from the system. We propose the notion that this effect as an indirect pathway of phage inhibition by bacteria with significant relevance for the clinical outcome of phage therapy.